Stigmatisasi Sosial Terhadap Komunitas LGBTQ di Indonesia: Perilaku Stigma Masyarakat Indonesia terhadap Komunitas LGBTQ di Indonesia - Arif, Arif Alwan (Triwikrama: Jurnal Ilmu Sosial, 2024)
The phenomenon of the Prophet Luth has returned to the time before the new order began. There is a potential for social stigma of Indonesian society towards the LGBTQ community. They have the potential to give something that is not wearing and give a certain label to the LGBTQ community. The stigma that will actually cause the spread of disease in the community to be more uncontrollable. The purpose of this research is to uncover some of the backgrounds why stigmatization of the LGBTQ community occurs in Indonesian society. This research is a qualitative descriptive research. The data collection is of course based on its relationship to the topic of discussion about LGBTQ. The results of this study are divided into three parts, including the definition and context of stigmatization in the form of presenting the concepts of stigmatization, cultural and religious contexts, as well as forms of stigmatization of Indonesian society towards the LGBTQ community in Indonesia